Legal effectiveness of independent waste management through waste banks in the City of Tegal as an effort to empower and care for the environment - Peggy Dian Septi Nur Angraini (The International Journal of Politics and Sociology Research, 2023)
Waste management for environmental concern can take advantage of the participation of the community. This research uses empirical research with descriptive qualitative which aims to find out and analyze the legal effectiveness of independent waste management through garbage banks in Tegal City as an effort to empower and care for the environment. The results of research on Waste Bank Management through the Implementation of the Indonesian Garbage Bank Association (ASOBSI) in Tegal City with 36 (thirty six) customers, Dewi Shinta Main Garbage Bank with 162 (one hundred and sixty two) customers and 8 (eight) unit waste banks and The Nusa Indah Unit Waste Bank in Tegal City with 80 (eighty) customers was established due to the concern of the surrounding community towards organic and inorganic waste. The Garbage Bank is tasked with serving the deposit of waste to be converted into a savings account, sorting waste according to type for economic value, selling waste, administration of waste bank bookkeeping, conducting education and development innovations for waste bank customers and the general public. The implementation of the waste bank independent waste management has been carried out effectively based on the mandate of laws and regulations with responsiveness, independence, community partnerships, economic value, education, achievements, although with limited assistance or no incentives, the management continues to carry out environmental management activities for waste.